MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH PESERTA DIDIK PADA PEMBELAJARAN MATEMATIKA MELALUI ALAT PERAGA SIMULASI BANJIR - Nandang Arif Saefuloh; Usep Kosasih; Rika Farida (Universitas Islam Nusantara, 2018)
Urgency of this research is implementation of constructivism based learning and Education for Suistainable Development(EfSD) that is by integrating constructivism based props with environmental issue in learning through discovery learningmodel learning. There’s a flood simulation tool created to improve the problem solving skills of learners on learningmathematics. The method in this research is experimental method by using quantitative approach, while the researchpopulation is all students of SMP YPU Bandung and sample of students study class VIII as much as two classes. Dataanalysis is done quantitatively. Quantitative analysis is performed on pre-test, post-test, and gains data normalized problemsolving abilities. Based on the analysts of the results of the study there are differences in the ability to solve mathematicalproblems among learners who learn with the model of discovery learning using the help of flood simulation aids and learnerswho learn with conventional learning, where the improvement of problem solving skills of mathematic learners who learnwith the help of simulation tools flood is better than learners who learn with conventional learning.